Prospective study of high-risk pregnancy and their outcome in tertiary care center - Nandimath, Savitri R.; Gaikwad, Priyanka; Yadav, Manisha; Patil, Bhushan A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Women form the centre of the family and their health is of prime importance to the well-being of the whole family. MCH status is assessed through measurements of mortality, morbidity, growth and development. The term “high risk pregnancy (HRP)” refers to any pregnancy associated with an increased risk for adverse outcomes which can be maternal or fetal. Methods: It was a prospective observational study conducted on all pregnant women admitted to labour ward in study period from 1st October 2018 to 30th September 2020. Results: In our study out of 17101 mothers admitted in the labour ward over 56.2 % belong to low-risk group, 25.5% to the moderate and 18.3% belong to high-risk group. Majority of patients belong the age group of 20- 24 years (56.6%) and 78.84% were primipara. Registered patients 98.4% whereas unregistered admissions were 1.6%. 92.95% of admissions were ≥37 weeks gestational age. The mode of delivery for 58.1% of the patients was vaginal deliveries whereas 41.9% delivered through LSCS. 95.10% of women had their babies with them after delivery while NICU admissions were 23.79%. Preterm admissions were seen maximum in high-risk group (26.67%) 52.5% of the patients belonging to the high-risk group were delivered by LSCS, among them 21.59% babies required NICU admission and neonatal death (3.50%) was also higher. Conclusions: Early detection of high-risk pregnancies at PHC level with proper ANC and referral system improves fetomaternal outcome.